Gimnazijski pouk književnosti v luči prenove in posodobitve - Žbogar, Alenka (Jezik in slovstvo, 2015)
In the article, the revised Grammar school curriculum for Slovene (2008) is compared with the revised syllabus for the Slovenian language and literature from 1996. It has been established that the continuity of the teaching of literature indicates the competence approach, while the novelty of the UN 2008 lies in its systemic approach. Both didactic approaches were defined by Boza Krakar Vogel.
Keywords: Krakar Vogel, Boža, 1950-; didaktika književnosti; učni načrti; gimnazije; prenova